Distribution of Hard Hematite Ore at the Quadilßtero Ferrffero, Minas Gerais, Brazil and its Possible Genetic Significance (The Australasian Institute of Mining and Metallurgy, 2002)
The hematite deposits of Quadrilßtero Ferrffero (QF) are hosted by the Proterozoic itabirites of the Itabira iron formation (Harder and Chamberlin, 1915). These deposits are widely distributed at QF and include the hard hematite ore bodies. However, considerable variations in ore structure and texture can be observed. A preserved banding and lamination in the thin bedded, compact hematite ore, apparently reflects the original layering and/or the prominent foliation of the partly or completely replaced itabirite. The structure of the hematite ore deposits varies from almond shaped, rootless, to bedded bodies, both concordant with the main foliation, and to mesoscopic veins and irregular bodies. Hematite ore textures, which depends on the structural characteristics of the deposit, may be grouped into four main types:thin bedded, laminated and banded; micaceous, foliated and schistose; brecciated; and compact/massive. Thin bedded ores occur in the western, central and subordinately eastern portions of QF, while submicaceous, micaceous and schistose ores are predominant at the eastern part. Brecciated ores exist mainly at the western part and subordinately in central QF. Structureless, compact hematite ores may be either related to the brecciated hematite or occur as isolated bodies at central QF. It is suggested that a synkinematic, acid and oxidant, metasomatism during metamorphism, under a ductile regime, was responsible for the hard hematite ores of the types 1 and 2, and a static, subsequent, hydrothermal, regional metasomatism, under brittle regime resulted in the formation of the types 3 and 4. The common texture present in the all ores is the ubiquitous magnetite porphyroclasts replacement by hematite. Quartz and other silicate minerals are also substituted by hematite. Muscovite, tourmaline, talc, chlorite, apatite and kaolinite have been recognised in the hard hematitic ores. Apparently that mineral association denotes different equilibrium conditions of formation.